SPATIAL ARRANGEMENTS FOR SUPER-EARLY GENOTYPES FOR COMMON BEAN PRODUCTION (Colloquium Agrariae. ISSN: 1809-8215, 2017)
The super-early genotypes (SEG) of common bean (Phaseolus vulgaris), developed by Embrapa Rice and Beans in Brazil, have a shorter life cycle (65-75 days) when compared with the full-season traditional cultivars (95-105 days). Spatial arrangements of plants for SEG should be evaluated to allow fully exploit their genetic potential. The aim of this study was to determine the effects of plant population and row spacing on grain yield and its components in super-early genotypes of common bean. The experimental design was a randomized block in a 2 x 2 x 5 factorial, with six replications, in two growing seasons (2014/2015 and 2015). The treatments consisted of the combination of two super-early genotypes of common bean (CNFC 15874 and CNFC 15875), two row spacings (0.35 and 0.45 m) and five plant densities (6, 10, 14, 18 and 22 seeds m-1). We also included a control treatment, IPR Colibri cultivar (65-75 days of life cycle) with 10 seeds m-1 density. The increase in plant density decreased yield components per plant but increased grain yield of super-early genotypes of common bean per unit area (from 1653 to 4614 kg ha-1 in 2014/2015 and from 2239 to 2537 kg ha-1 in 2015). The spatial arrangement of sowing density of 22 seeds per meter and 0.45 m row spacing allowed the highest grain yield in super-early genotypes of common bean.